Water absorption of recycled aggregates: Measurements, influence of temperature and practical consequences. (November 2020) - Théréné, Florian; Keita, Emmanuel; Naël-Redolfi, Jennifer; Boustingorry, Pascal; Bonafous, Laurent; Roussel, Nicolas
Abstract: Recycled Concrete Aggregates are highly porous and may therefore absorb more water than natural aggregates. Several methods allow for the measurement of water absorption requiring drying at temperature above ambient conditions. We show here that, for temperatures above the ambient temperature (>30 °C) and at low relative humidity, the drying of recycled aggregates removes some bounded water contained in hardened cement paste and increases both measured porosity and water absorption. Porosity and XRD suggest that porosity increases due to ettringite dehydration. Thus, the drying step required to characterize recycled aggregates leads to a systematic overestimation of the water absorption. Moreover, this overestimation induces an error in mix-design leading to a higher effective water/cement ratio. If absorption and water content are measured with the same preparation protocol, correction is not needed. We finally propose a correction method for the water absorption measured according to the standard protocol (drying at 105 °C).